Multilayered Representation: Taking Multiple Discursive Addressings Seriously in Politics. Issue 3 (3rd July 2019) - Barreto, Rachel Cardoso; Mendonça, Ricardo Fabrino
ABSTRACT: This paper employs a constructivist approach to representation to investigate the representative claims of Members of Parliament in a state legislature of Minas Gerais in Brazil. It argues that parliamentary discourses should be thought of as utterances addressing multiple audiences at the same time, and, thus, mobilising diverse layers in the everyday construction of representation. It focuses on some underdeveloped points in the concept of shape-shifting representation, advocated by Saward ([2014]. Shape-shifting representation. American Political Science Review, 108(4), 723–736.). The analysis has shown that the idea of multiple layers may be interpretively fruitful.